2019
DOI: 10.3390/medicina55080413
|View full text |Cite
|
Sign up to set email alerts
|

The Measurement of Elderly Volunteers’ Optic Nerve Sheath Diameters by Ocular Ultrasonography

Abstract: Background and objectives: The optic nerve is a component of the central nervous system, and the optic nerve sheath is connected to the subarachnoid space. For this reason, intracranial pressure (ICP) increases are directly transmitted to the optic nerve sheath. Knowing the normal optic nerve sheath diameter (ONSD) range in a healthy population is necessary to interpret this measurement as a sign of intracranial pressure in clinical practice and research. In this study, we aimed to determine the standard ONSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…One previous study reported that in children, ONSD increases with age until the age of 10 years (7,21). Furthermore, some studies have found no difference in the ONSD between different ages in healthy adults (1,6,22). Our results were similar, whereby ONSD was not correlated with age in the participants in the control group.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One previous study reported that in children, ONSD increases with age until the age of 10 years (7,21). Furthermore, some studies have found no difference in the ONSD between different ages in healthy adults (1,6,22). Our results were similar, whereby ONSD was not correlated with age in the participants in the control group.…”
Section: Discussionmentioning
confidence: 98%
“…An enlarged ONSD is regarded as an undisputed imaging sign that is suggestive of an elevated ICP (25). The anatomical connection between the optic nerve sheath and the subarachnoid space make the direct transmission of an ICP increase to the optic nerve sheath possible (6).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, there is still no consensus on cut-off values in the detection and monitoring of increased ICP, which is the most common reason for ONSD measurement. 4 False positive and false negative results are mentioned in some studies investigating the usefulness of the transorbital ultrasonographic ONSD measurement in different clinical situations. [22][23][24][25] In a study conducted with 102 patients to investigate the relationship between ONSD values and increased ICP, false negative results were obtained in 9.6% and false positivity in 8.2% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…6 In elderly volunteers, the right-left ONSD difference was 0.15 ± 0.17 mm in women and 0.18 ± 0.19 mm in men. 4 Therefore, there appears to be a difference between the right and left ONSDs not only in patients but also in healthy adults, and this difference may increase in the presence of an intracranial event. In the present study, the right-left ONSD difference was 0.05 ± 0.05 mm in the patients with no grade difference between the right and left ICA, 0.55 ± 0.32 mm in those with a single-grade difference, and 0.78 ± 0.39 mm in those with a twograde difference.…”
Section: T a B L E 1 Characteristics Of Control Group And Patientsmentioning
confidence: 99%
See 1 more Smart Citation